A survey of innovative teaching approaches in the University of the Philippines elementary school - Ratanasee, Ketsuda 1941- ([Quezon City s.n], 1974)
The innovative teaching approaches used in the University of the Philippines Elementary School were identified in this study. Its implications for Thailand were derived.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Philippines. University. Elementary School; Teaching